2003
DOI: 10.1046/j.1365-2990.2003.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐dependent and caspase‐independent signalling of apoptosis in the penumbra following middle cerebral artery occlusion in the adult rat

Abstract: Transient focal ischaemia by middle cerebral artery occlusion (MCAO) may produce cell death, but the mechanisms leading to cell death differ in the infarct core and in the penumbra, the immediate zone surrounding the infarct core. In the present study, transient focal ischaemia to adult rats was produced by intraluminal occlusion of the middle cerebral artery for 1 h followed by 0 h (n=6), 1 h (n=10), 4 h (n=8), 6 h (n=2) and 12 h (n=3) of reperfusion. The present model of ischaemia causes a large cortico-stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 29 publications
7
65
0
1
Order By: Relevance
“…This finding with AIF immunoblotting is consistent with immunohistochemical detection of nuclear AIF in a small percent of cells by 1 hour of reperfusion and a larger increase that occurs by 4-8 hours of reperfusion after 45 minutes of MCAO in the mouse (Plesnila et al, 2004). Nuclear staining for AIF has also been reported in the rat brain at 4 hours of reperfusion after 1 hour of MCAO (Ferrer et al, 2003). An increase in the production of reactive oxygen species (ROS) leads to DNA damage and activation of PARP after MCAO (Zhang et al, 1994;Eliasson et al, 1999).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This finding with AIF immunoblotting is consistent with immunohistochemical detection of nuclear AIF in a small percent of cells by 1 hour of reperfusion and a larger increase that occurs by 4-8 hours of reperfusion after 45 minutes of MCAO in the mouse (Plesnila et al, 2004). Nuclear staining for AIF has also been reported in the rat brain at 4 hours of reperfusion after 1 hour of MCAO (Ferrer et al, 2003). An increase in the production of reactive oxygen species (ROS) leads to DNA damage and activation of PARP after MCAO (Zhang et al, 1994;Eliasson et al, 1999).…”
Section: Discussionsupporting
confidence: 85%
“…This design permitted evaluation at early reperfusion, at a mid-range of reperfusion, when many neurons show ischemic morphologic changes, and at late reperfusion, when cell death is widespread throughout the maturing infarct. These timepoints spanned the 1-8 hour range for AIF translocation reported by others (Ferrer et al, 2003;Plesnila et al, 2004;Zhao et al, 2004;Culmsee et al, 2005). Two hemispheres were used per lane.…”
Section: Subcellular Fractionation and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of DYX1C1 expression in ischemic brain tissue suggested that it is involved dynamically in the functional cell state, changing in the face of metabolic challenge. Similar changes in protein distribution in ischemia have been observed for the Elk-1 transcription factor (39). These results from human cerebral ischemia warrant more systematic studies on the role of DYX1C1 in cell stress and ischemia as well as dyslexia.…”
Section: Discussionsupporting
confidence: 68%
“…Caspase-3 is considered to be the significant target for prevention of acute cerebral infarction because of its major role in ischemia and induction of apoptosis [23,24]. In the current Figure 3: 5,7-Dimethoxycoumarin prevents increase in apoptosis index in the rats with acute cerebral infarction.…”
Section: Discussionmentioning
confidence: 78%